Impact of agricultural cooperatives on smallholders' technical efficiency: empirical evidence from Ethiopia - Abate, Gashaw T.; Francesconi, Gian N.; Getnet, Kindie (Wiley, 2014)
Using household survey data from Ethiopia, this paper evaluatesthe impact of agricultural cooperatives on smallholders’ technical efficiency. We usedpropensity score matching to compare the average difference in technical efficiencybetween cooperative member farmers and similar independent farmers. The resultsshow that agricultural cooperatives are effective in providing support services thatsignificantly contribute to members’ technical efficiency. These results are found to beinsensitive to hidden bias and consistent with the idea that agricultural cooperativesenhance members’ efficiency by easing access to productive inputs and facilitating ex-tension linkages. According to the findings, increased participation in agriculturalcooperatives should further enhance efficiency gains among smallholder farmers.